1997
DOI: 10.1021/ja963788n
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated Cyclic and Acyclic Keto−Enol Systems:  A Remarkable Contrast

Abstract: Recent reports from this laboratory have revealed that highly fluorinated 4- and 5-membered-ring enols are comparable in stability to, or more stable thermodynamically than, the corresponding ketones, even in non-Lewis-basic media. Work on perfluorinated keto−enol systems has now been extended to 2H-perfluorocyclohexanone plus its enol and to a series of acyclic analogues. In carbon tetrachloride, K E/K = 0.33 (22 °C) for the six-ring system, but only enol is detectable in Lewis-basic solvents. This shift is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…The stability of enol is a result of the destabilization of ketone. This result agrees with previous work on trifluorocyclopropanone (perfluorination) [16]. The calculated charge distribution in 2H-perfluorocyclopropanone 5, obtained from the electron density (Table 4), may give a plausible explanation for its destabilization.…”
Section: Relative Stability Of the Fluorinated Cyclopropanonecycloprosupporting
confidence: 91%
See 1 more Smart Citation
“…The stability of enol is a result of the destabilization of ketone. This result agrees with previous work on trifluorocyclopropanone (perfluorination) [16]. The calculated charge distribution in 2H-perfluorocyclopropanone 5, obtained from the electron density (Table 4), may give a plausible explanation for its destabilization.…”
Section: Relative Stability Of the Fluorinated Cyclopropanonecycloprosupporting
confidence: 91%
“…Cyclopropanone and its substituted precursors have never been studied as keto-enol tautomeric systems, except perfluorinated cyclopropanone [16]. This perfluorination was studied by ab initio calculations and has shown that the enol form should be present in substantial concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…[53] Ethyl 2-fluoroacetoacetate and ethyl 2-fluorobenzoylacetate are enolized to the extent of 4 % and Ͻ 3 %, respectively, [52] less than half as much as the corresponding parent compounds. [53][54] Spectacular substituent effects on the oxo/enol equilibria of polyfluoroketones were reported by Lemal et al [55] Whereas the enol forms of both cyclopentanone and 3H-heptafluoro-2-butanone were present only in undetectably small concentrations, 2H-nonafluorocyclohexanone, 2,2-H 2 -hexafluorocyclopentanone, 2H-heptafluoropentanone and 2H-pentafluorocyclobutanone were enolized to the extent of 25, 13, 99 and Ͼ99.5 %. [55] The structures of uracil and of the cancer drug 5-fluorouracil have also been extensively investigated.…”
Section: Introductionmentioning
confidence: 67%
“…[53][54] Spectacular substituent effects on the oxo/enol equilibria of polyfluoroketones were reported by Lemal et al [55] Whereas the enol forms of both cyclopentanone and 3H-heptafluoro-2-butanone were present only in undetectably small concentrations, 2H-nonafluorocyclohexanone, 2,2-H 2 -hexafluorocyclopentanone, 2H-heptafluoropentanone and 2H-pentafluorocyclobutanone were enolized to the extent of 25, 13, 99 and Ͼ99.5 %. [55] The structures of uracil and of the cancer drug 5-fluorouracil have also been extensively investigated. According to an early ab initio calculation at the 3-21G level, the tautomeric population of the parent heterocycle and its fluorinated congener turned out to be almost identical.…”
Section: Introductionmentioning
confidence: 67%
“…Remarkably, the pair 8.25A and 8.25B in Figure 8.25 cannot be equilibrated by acid or base; the enol 8.25A, for example, can be distilled from concentrated sulphuric acid. Enols of cyclic systems are also unusually stable [123] and the equilibrium constant depends on the solvent (Figure 8.26). Clearly, the tautomerism is inhibited by a kinetic barrier and this could be the relative instability of the anion 8.25C, where electron-pair repulsion involving non-bonding pairs on fluorine could be significant.…”
Section: Synthesismentioning
confidence: 99%